Bone Marrow-Derived Macrophages from AβPP/PS1 Mice are Sensitized to the Effects of Inflammatory Stimuli. - LYNCH, MARINA; MINOGUE, AEDIN; MINOGUE, AEDIN; LYNCH, MARINA ANNETTA (My University, 2015)
Macrophages are key cells in tissue defense in the periphery and, under certain circumstances, infiltrate the central nervous system, where they may play a similar role in the brain, perhaps supporting the function of microglia. Macrophages have been shown to adopt different activation states in response to various stimuli. Specifically, when exposed to inflammatory stimuli such as interferon (IFN)γ, the cells adopt the M1 phenotype, whereas when exposed to anti-inflammatory cytokines such as interleukin (IL)-4 or IL-13, the M2 phenotype is adopted. While M1 macrophages are associated with tissue defense and destruction of invading pathogens, M2 macrophages are involved in tissue repair and in terminating inflammation. It is well known that an inflammatory microenvironment exists in the brain of aged animals and also in the brain of mice that overexpress amyloid-β protein precursor (AβPP) and presenilin 1 (PS1; AβPP/PS1 mice), a commonly-used model of Alzheimer's disease (AD). Recent studies have revealed that immune cells, including macrophages, infiltrate the brain in both circumstances raising the possibility that these cells adopt the M1 activation state and contribute to the already-existing neuroinflammation. We set out to examine the responses of bone marrow-derived macrophages prepared from wildtype and AβPP/PS1 mice and demonstrate that cells from AβPP/PS1 mice, even after several days in culture, respond more profoundly to IFNγ than those from wildtype mice. We suggest that this propensity to respond to M1-polarizing stimuli, together with the described changes in the brain of AβPP/PS1 mice, contribute to the development of chronic neuroinflammation
PUBLISHED
PMID: 25374107
Keywords: neuroinflammation; bone marrow-derived macrophages; blood-brain barrier; M1 and M2 phenotypes; IFNγ; AβPP/PS1 mice; Ageing; Immunology, Inflammation & Infection; Neuroscience; Age related diseases; Neuroscience